THE EFFECT OF DEBT CHOICE ON FIRM VALUE - Juwono, Hans Putra; Santoso, Eko Budi (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. This study aims to examine the impact of the choice of bank debt and bond debt on firm value of infrastructure sector companies. This research is important because it makes a significant contribution to the academic literature and financial practitioners, as well as being a guide for managers in making corporate financial decisions. Research Methods. Secondary data in this study were taken from 62 companies during the 2021-2022 period with total of 112 samples were tested using multiple linear regression analysis method. Research Results and Findings. The results showed that the choice of debt has an effect on firm value. Specifically, companies that choose bond debt have a higher firm value than those that choose bank debt. This happens because higher transparency in bond debt contributes positively to firm value. Therefore, bond debt is more profitable for infrastructure sector companies.